On the Waterfront: The Historic Waterfront Precinct, Dunedin, New Zealand - Alexander Trapeznik (Public History Review, 2011)
This article examines the industrial and mercantile built heritage of New Zealand by considering a remarkable precinct in Dunedin of surviving commercial buildings from the second half of the nineteenth century. The city was then the country’s financial, commercial and industrial centre, having undergone a gold rush boom in the 1860s. A large industrial and commercial precinct was rapidly created on reclaimed land in the central city over the following three decades. This study seeks to emphasise the importance of the agricultural economy and the stock and station agency business in particular to urban growth; this urban-rural interdependency that shaped nineteenth-century Dunedin. This contradicts the common emphasis on the gold rush boom and its architectural legacy. This study adopts a landscapes approach, offering a holistic framework which recognises the inter-relationship of